2020
DOI: 10.1007/jhep07(2020)014
|View full text |Cite
|
Sign up to set email alerts
|

Testing lepton flavor models at ESSnuSB

Abstract: We review and investigate lepton flavor models, stemming from discrete non-Abelian flavor symmetries, described by one or two free model parameters. First, we confront eleven one-and seven two-parameter models with current results on leptonic mixing angles from global fits to neutrino oscillation data. We find that five of the one-and five of the two-parameter models survive the confrontation test at 3σ. Second, we investigate how these ten one-and two-parameter lepton flavor models may be discriminated at the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Such studies crucially depend on the breaking pattern of G f into its residual subgroups for charged lepton sector G e and neutrino sector G ν . For example, in [284], the authors have studied implication of breaking of G f × CP (with G f = A 4 , S 4 , A 5 ) into G e > Z 2 , G ν = Z 2 × CP in the context of ESSnuSB experiment [285]. Such breaking pattern is usually observed in the semi-direct approach of flavor model building [286].…”
Section: B Flavor Symmetry and Neutrino Experimentsmentioning
confidence: 99%
“…Such studies crucially depend on the breaking pattern of G f into its residual subgroups for charged lepton sector G e and neutrino sector G ν . For example, in [284], the authors have studied implication of breaking of G f × CP (with G f = A 4 , S 4 , A 5 ) into G e > Z 2 , G ν = Z 2 × CP in the context of ESSnuSB experiment [285]. Such breaking pattern is usually observed in the semi-direct approach of flavor model building [286].…”
Section: B Flavor Symmetry and Neutrino Experimentsmentioning
confidence: 99%
“…The presence of mixing sum rules significantly increases the testability of flavor models and can guide the requirements on the target precision for the measurements of the mixing parameters. Indeed, with the help of mixing sum rules one can forecast the impact of measurements at future neutrino oscillation experiments [28][29][30][31][32][33][34][35] like DUNE, T2HK, ESSνSB, and JUNO.…”
Section: Discrete Symmetriesmentioning
confidence: 99%
“…The corresponding mixing patterns are characterized by one free angle parameter. See [35] for a summary of such scenarios and original references.…”
Section: Precision Measurements Of Mixing Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrino mass sum rules can be tested in experiments measuring the absolute neutrino mass scale or experiments that provide information on the sum of the neutrino masses. A number of studies have shown, in particular, that checking the validity of the leptonic mixing sum rules using the currently available and prospective data on the neutrino mixing angles and the Dirac CPV phase is an extremely powerful method of discriminating between different discrete symmetry models and, more generally, of testing the non-Abelian discrete symmetry approach to the neutrino mixing problem (see, e.g., [32][33][34][35]).…”
Section: Jhep03(2021)177mentioning
confidence: 99%